3
$\begingroup$

In the book I am reading, I have encountered the following sum.

$$S = \sum_{n=1}^{2019}{\frac{1+2+3+4...+n}{1^3+2^3+3^3...+2019^3}}$$

From here, I factored the denominator since it does not seem to be dependent on $n,$ and I rewrote the expression as

$$\frac{1}{1^3+2^3+3^3+ \cdots +2019^3} \sum_{n=1}^{2019}{1+2+3+4+ \cdots +n}=\frac{1}{1^3+2^3+3^3 + \cdots +2019^3} \sum_{n=1}^{2019}{\sum_{k=1}^n}k$$

From here, I proceeded to compute the sum since there is an equation for the sum of the first $n$ terms, and then, I solved the sum of this equation. Also, I applied the equation of the sum of the first $n^3$ terms. Finally, my result was wrong. My question is regarding my initial approach to the problem since everything else is very simple. I have thought about other ways to solve this, and I can not find it. The official answer is $$\frac{2019}{2010}.$$ Give this problem a try, and if you arrive at the solution, I invite you to help me understand it.

$\endgroup$
  • $\begingroup$ Your questions has some errors and you have done a calculation mistake $\endgroup$ – UmbQbify -Key20- Jun 30 at 14:21
  • 1
    $\begingroup$ Could you be more specific on where? $\endgroup$ – Samuel A. Morales Jun 30 at 14:23
  • $\begingroup$ Minor spelling mistakes : initial , denominator. And I think the The official Answer is wrong itself, it should be $\frac{2\cdot 2011}{2019\cdot 2010}$ but I could be wrong $\endgroup$ – UmbQbify -Key20- Jun 30 at 14:29
  • $\begingroup$ Instead of $\sum\limits_{k=1}^nk$, I think it should be $\sum\limits_{k=1}^n\frac{k^2+k}2$ $\endgroup$ – robjohn Jun 30 at 23:16
  • $\begingroup$ Could you tell me why? I do not see it as clearly $\endgroup$ – Samuel A. Morales Jul 1 at 0:19
5
$\begingroup$

Let's replace $2019$ by $T$. In the numerator:

$$ \sum_{n=1}^T \sum_{k=1}^n k = \sum_{n=1}^T \frac{n(n+1)}{2} = \frac{(T+1)^3 - (T+1)}{6}$$

In the denominator:

$$ \sum_{k=1}^T k^3 = \frac{(T+1)^4 - 2 (T+1)^3 + (T+1)^2}{4} $$

So:

$$ \frac{ \sum_{n=1}^T \sum_{k=1}^n k }{\sum_{k=1}^T k^3} = \frac{4}{6} \frac{(T+1)^3 - (T+1)}{(T+1)^4 - 2 (T+1)^3 + (T+1)^2} = \frac{2 (T+2)}{3 T (T+1)}$$

For $T=2019$ this is $\dfrac{2021}{3030 \cdot 2019}$. The official answer is wrong.

Or maybe the question was supposed to be $$ \frac{1}{2}\sum_{n=1}^{2019} \frac{1 + 2 + \ldots + n}{1^3 + 2^3 + \ldots + n^3} $$ which would work out to $\dfrac{2019}{2020}$.

| cite | improve this answer | |
$\endgroup$
0
$\begingroup$

Like you mentioned, the denominator is independent of $n,$ hence we can consider it separately. We have that $D = 1^3 + 2^3 + \cdots + 2019^3 = \sum_{i = 1}^{2019} i^3.$ Observe that $S$ can be written as $$\begin{align*} S = \frac 1 D \sum_{n = 1}^{2019} (1 + 2 + \cdots + n) &= \frac 1 D \sum_{n = 1}^{2019} \sum_{k = 1}^n k \\ \\ &= \frac 1 D \sum_{n = 1}^{2019} \frac{n(n + 1)} 2 \\ \\ &= \frac 1 {2D} \biggl(\sum_{n = 1}^{2019} n^2 + \sum_{n = 1}^{2019} n \biggr) \\ \\ &= \frac 1 {2D} \biggl(\frac {2019 \cdot 2020 \cdot 4039} 6 + \frac {2019 \cdot 2020} 2 \biggr) \end{align*}.$$ One can evaluate $D$ using the sum of cubes formula $\sum_{k = 1}^n k^3 = \frac{n^2 (n + 1)^2} 4$ to find that $S = \frac{2021}{6117570}.$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.